2011
DOI: 10.1097/jcp.0b013e318218dcd5
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Inpatient, Phase 2, Double-Blind, Placebo-Controlled Dose-Ranging Study of LY2140023 Monohydrate in Patients With DSM-IV Schizophrenia

Abstract: The primary objective of this study was to test the hypothesis that 1 or more dose levels of LY2140023 monohydrate, an oral prodrug of the potent metabotropic glutamate (mGlu) 2/3 receptor agonist LY404039, given to patients with schizophrenia for 4 weeks would demonstrate significantly greater efficacy than placebo. The HBBI study was a multicenter, randomized, double-blind, parallel, placebo- and active-controlled trial. Male and female patients aged 18 to 65 years who met the Diagnostic and Statistical Manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
153
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(161 citation statements)
references
References 12 publications
5
153
1
Order By: Relevance
“…The efficacy of heterotropic agonists in this PCP model was observed in mGluR3 but not mGluR2 knock-out mice, consistent with their activation of mGluR2 in vitro (31)(32)(33)(34). Although mGluR2/3 agonists and mGluR2-positive allosteric modulators represent a potentially efficacious mGluR2-targeted antipsychotic therapy (35,36), data from animal models of schizophrenia suggest that NAAG peptidase inhibition represents a related but distinctly different pharmacotherapy based on activation of mGluR3 (12,26). The present study was initiated to test the hypothesis that, consistent with the glutamate theory of this disorder, NAAG peptidase inhibitors also block the PCP-induced increase in glutamate release in the mPFC and NAc, brain regions associated with the behavioral and neurochemical effects of PCP and schizophrenia (1,(37)(38)(39)(40).…”
supporting
confidence: 62%
“…The efficacy of heterotropic agonists in this PCP model was observed in mGluR3 but not mGluR2 knock-out mice, consistent with their activation of mGluR2 in vitro (31)(32)(33)(34). Although mGluR2/3 agonists and mGluR2-positive allosteric modulators represent a potentially efficacious mGluR2-targeted antipsychotic therapy (35,36), data from animal models of schizophrenia suggest that NAAG peptidase inhibition represents a related but distinctly different pharmacotherapy based on activation of mGluR3 (12,26). The present study was initiated to test the hypothesis that, consistent with the glutamate theory of this disorder, NAAG peptidase inhibitors also block the PCP-induced increase in glutamate release in the mPFC and NAc, brain regions associated with the behavioral and neurochemical effects of PCP and schizophrenia (1,(37)(38)(39)(40).…”
supporting
confidence: 62%
“…A four-week trial had little or no efficacy against positive symptoms or negative signs when compared with olanzapine. 34,35 While there does not at present appear to be a significant role for glutamate receptors in the antipsychotic treatment of schizophrenia, these are only limited studies, and much remains to be learned about the possible benefit of this approach. Table 1, this high value for clozapine and a similar high value for quetiapine immediately indicated that these two drugs had K i values higher than any of the other antipsychotics and likely had a unique mechanism of interaction with the D2 receptor, namely, "loose binding to the D2 receptor".…”
Section: Clozapine and Glutamate Receptorsmentioning
confidence: 99%
“…These agonists have a more favorable safety profile. Unlike current treatments, pomaglumetad was well tolerated and had a low incidence of extrapyramidal symptoms (EPS), hyperprolactinemia, and weight gain [24,25,27,28].…”
Section: Metabotropic Glutamate Receptor Agonistsmentioning
confidence: 99%
“…The trial did not achieve interpretable results, however, as both pomaglumetad and the active control, olanzapine, failed to separate from placebo due to an unusually high placebo response [25]. An additional phase II trial examined pomaglumetad as a monotherapy in acute psychotic exacerbations in schizophrenia.…”
Section: Metabotropic Glutamate Receptor Agonistsmentioning
confidence: 99%